The Crisis We Are Not Talking About: One-in-Three Annual HIV Seroconversions Among Sexual and Gender Minorities Were Persistent Methamphetamine Users. (1st November 2020) - Grov, Christian; Westmoreland, Drew; Morrison, Corey; Carrico, Adam W.; Nash, Denis
Abstract : Introduction: Methamphetamine use is once again on the rise among sexual and gender minorities who have sex with men (SGMSM). Methods: Baseline and 12-month data are taken from an ongoing cohort study of n = 4786 SGMSM aged 16–49 at risk for HIV from across the United States. Participants completed annual online surveys and at-home HIV testing (oral fluid samples returned through mail). Results: Overall, 2.47 per 100 persons seroconverted over 12 months. In addition, 13.8% of participants reported any methamphetamine use over the 12-month study period. Nearly three-fourths (74.7%; 422 of 565) of those who reported using methamphetamine at baseline were persistent users at 12 months. In adjusted analyses, compared with those who did not use methamphetamine, incident methamphetamine users (ie, those who indicated use between baseline and follow-up) and persistent methamphetamine users had significantly higher odds of HIV seroconverting (adjusted odds ratio = 3.95, 95% confidence interval: 1.64 to 9.47; and 7.11, 4.53 to 11.17, respectively). Persistent methamphetamine users accounted for one-third of all observed HIV seroconversions (41 of 115). Discussion: Among SGMSM at elevated risk for HIV, persistent methamphetamine use was prevalent and associated with substantially amplified risk for HIV seroconversion. Expanded efforts are needed to test implementation strategies for scalable, evidence-based interventions to reduce HIV risk in SGMSM who use methamphetamine.